Does endophyte symbiosis resist allelopathic effects of an invasive plant in degraded grassland?. (October 2015) - Bao, Gensheng; Saikkonen, Kari; Wang, Hongsheng; Zhou, Lianyu; Chen, Shuihong; Li, Chunjie; Nan, Zhibiao
Abstract: Allelopathic effects and plant associated systemic endophytic fungi are often thought to play a role in the invasion of exotic plant species. Here, we tested the inhibitory effects of the aqueous extracts of the hemiparasitic weed Pedicularis kansuensis on seed germination and seedling growth of endophyte-free (E−) and -infected (E+) grass species, Stipa purpurea and Elymus tangutorum . The weed extracts significantly inhibited both seed germination and seedling growth of the target grass species. Extracts from the inflorescences gave greater inhibition than those from the stems or roots, while the concentration of the extract had a direct effect on the extent of inhibition. The E+ target plants were less susceptible to the extracts than their E-counterparts. Our results suggest that the allelopathic potential of P. kansuensis will lead to increased frequencies of endophyte infected plants in grass populations.